doc2a and doc2b contribute to locomotor and social behaviors by down-regulating npas4b in zebrafish - Yali Chi; Tao Feng; Zixin Du; Ping Huang; Wenjun Yu; Haihua Liu; Wanshan Wang; Xinping Yang; Liping Huang (BMC Biology)
Abstract Background Copy number variations (CNVs) occurring on chromosome 16p11.2 are associated with various neurodevelopmental disorders, including autism spectrum disorder (ASD), schizophrenia, and intellectual disability. Among the genes situated within the critical CNV region, DOC2A is noteworthy. We generated frameshift mutations in doc2a (double C2-like domain-containing protein a) and its paralog doc2b (double C2-like domain-containing protein b) in zebrafish via CRISPR-Cas9 respectively and obtained double-mutant doc2a −/− doc2b −/− by mating the single-mutant doc2a +/+ doc2b −/− and doc2a −/− doc2b +/+ zebrafish. Results doc2a −/− doc2b −/− mutants displayed aberrant morphology including tail bending and deformity, and morphologically normal individuals displayed aberrant behaviors, including reduced locomotion activity, impaired social interaction, and irregular movements. Whole-brain transcriptome sequencing of both wild-type and doc2a −/− doc2b −/− mutants revealed differentially expressed genes (DEGs) enriched with ASD candidate genes and synaptic signaling pathways, notably down-regulated gene npas4b (Neuronal PAS domain protein 4b). We found the downstream targets of the transcription factor Npas4b in the DEGs were mostly enriched in the synaptic signaling pathways. The npas4b knockout and knockdown zebrafish showed reduced locomotion activity and impaired social interaction similar to the behaviors observed in doc2a −/− doc2b −/− mutants. Conclusions This study suggests that DOC2A in the critical region of 16p11.2 may contribute to the pathogenesis of autism by interacting with other genes, such as DOC2B, and that the downregulation of NPAS4 may play an important role in autism.